The effect of readability and language choice in management accounting reports on risk-taking: an experimental study - Ewgenij Besuglov; Nils Crasselt (Journal of Business Economics, 2020)
Concisely written financial documents facilitate information processing and help to improve decision-making. However, the role of readability seems to be still neglected in accounting practice. Readability concerns become even more relevant in the light of the fact that English is commonly used as the corporate language in multinational corporations throughout the world. Management reports prepared in a foreign language may be less readable than reports written in the preparer's mother tongue. With this study we set out to experimentally investigate the effects of report readability and choosing either managers' mother tongue or a foreign language as the reporting language on risk-taking in a management accounting context. We were able to show that a low level of readability significantly reduces the willingness to accept beneficial risks, a phenomenon which can be explained by the cognitive load effect. In line with the foreign language effect, we provide tentative evidence that the use of a foreign language in combination with a high readability level enhances the willingness to undertake beneficial risks. Further investigation revealed that the foreign language effect is present only for a medium–high language proficiency level and can be best explained by the reduced emotionality account.
Keywords: M16; M40; 650; Cognitive load effect; Foreign language effect; Management accounting reporting; Readability; Risk-taking